2015
DOI: 10.4236/mrc.2015.42006
|View full text |Cite
|
Sign up to set email alerts
|

Green and Sustainable Heterogeneous Organo-Catalyst for Asymmetric Aldol Reactions

Abstract: Linear amino acids covalently supported on graphene sheet were employed as catalysts for asymmetric aldol reactions between cyclohexanone and aldehydes (aliphatic and/or aromatic) in a batch type reactor in the presence of water. The reactions were found to exhibit high yield as well as excellent ee value. Additionally, the catalysts were found to be truly heterogeneous and eco-friendly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Our group previously reported linear amino acids covalently immobilized on graphene sheet as catalysts for asymmetric aldol reactions between cyclohexanone and various aldehydes. The reactions were found to exhibit high yields as well as excellent ee values [22].…”
Section: Introductionmentioning
confidence: 93%
“…Our group previously reported linear amino acids covalently immobilized on graphene sheet as catalysts for asymmetric aldol reactions between cyclohexanone and various aldehydes. The reactions were found to exhibit high yields as well as excellent ee values [22].…”
Section: Introductionmentioning
confidence: 93%
“…27,28 In 2015, Sadiq and coworkers found that the direct asymmetric aldol reaction of cyclohexanone with aromatic and aliphatic aldehydes performed in aqueous media could be catalyzed by amino acids covalently attached to graphene. 29 Heterogeneous, porous, and recyclable carbocatalysts (which can be considered organocatalysts) afforded aldol adducts with excellent yields (up to 97%) and stereoselectivity (up to 23:1 dr with the anti diastereomer predominating, and up to 99% ee, Figure 2). Chiral catalysts were obtained from Lalanine, L-serine, L-valine and L-arginine covalently attached to a graphene sheet in a three-step procedure initiated by Hummers' and Offeman's oxidation method.…”
Section: Additions To Carbonyl Compoundsmentioning
confidence: 99%
“…[1,2] Given the guiding principles of Green Chemistry, heterogeneous organocatalystbased protocols, have proved to be sustainable protocols and are extensively in use for the synthesis of organic compounds. [3][4][5] Among the numerous reported protocols for developing heterogeneous organocatalysts, immobilizing and/ or impregnating the homogeneous catalysts onto several types of support materials is one of the most explored and established protocols. Polymers/frameworks like covalent organic frameworks (COFs), metal-organic frameworks (MOFs), covalent organic polymers (COPs), etc., and those occurring in nature like xanthan gum, cellulose, chitosan, alginate, etc., have been extensively used as support material in the development of heterogeneous organocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…For many decades after the term “catalysis” was coined, homogeneous catalysts were extensively used for catalyzing chemical reactions, but due to shortcomings associated with them such as difficulty in their recovery from the reaction solution, poor thermochemical stability, high operational cost, and lower reusability as well as the growing global concern for green and sustainable catalytic protocols, especially for pharmaceutical and agrochemical industries made the researchers look for better alternatives which led to the systematic design and development of a new class of catalysts known as heterogeneous organocatalysts [1,2] . Given the guiding principles of Green Chemistry, heterogeneous organocatalyst‐based protocols, have proved to be sustainable protocols and are extensively in use for the synthesis of organic compounds [3–5] . Among the numerous reported protocols for developing heterogeneous organocatalysts, immobilizing and/or impregnating the homogeneous catalysts onto several types of support materials is one of the most explored and established protocols.…”
Section: Introductionmentioning
confidence: 99%